Analysis of Carbon Monoxide (CO) Quality Due to the Construction of the Miftahun Najah Islamic Boarding School - Muhamad Fadli; Peppy Herawati; Hadrah; Endi Adriansyah; Rifqi Sufra; Muhammad Syaiful (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2022)
Air pollution comes from construction activities in the development of educational infrastructure buildings because it has an impact on changes in green open space and an increase in air pollution, especially Carbon Monoxide (CO) emissions in the air. The contribution of increasing CO2 and CO emissions can be sourced from all activities of workers who use energy such as procurement of building materials, use of transportation fuels, electricity use activities, and LPG use activities. Carbon footprint is a measure of the total amount of carbon dioxide (CO2) emissions that come from activities or accumulations from daily activities. This study aims to determine the amount of carbon Monoxide (CO) and CO2 emissions as indicators of air quality at the Miftahun Najah Islamic Boarding School. Measurement of Carbon Monoxide (CO) parameters was carried out for one week with 7 samplings in the morning and samplings in the afternoon in situ. Measurements using the Lutron GCO-2008 CO meter and carbon footprint calculations using the IPCC 2006 method. The measurement results were obtained in the afternoon with a total of 9,926 mg/Nm3 and the lowest in the morning was 1,102 mg/Nm3. Air temperature in the morning to evening ranged from 29oC – 36oC. The results showed that the concentration of Carbon Monoxide in the development of Islamic boarding school buildings was still below the quality standards set according to Government Regulation No. 22 of 2021, namely10,000 μg / Nm3.